The Accuracy Prediction of Cataract Surgery Refractive Results Using SRK/T and Haigis Formulas (with and without Personalized Constants) - Dewi Megasari Juhrie; Mayasari Wahyu; Andrew M Knoch (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: Fourth generation of IOL calculation formula (Haigis formula) calculates the ACD which is important in determining the IOL position, so the calculation results expected to be more accurate than the previous generation formula. Haigis formula uses 3 constants that can be updated (optimal/personalized constants). This study aimed to compare the accuracy prediction of cataract surgery refractive results using SRK/T and Haigis formulas (with and without personalized constant).Methods: This is an analytic prospective comparative study. We used 198 medical records data to calculate the Haigis personalized constants. Keratobiometry examinations were performed to 23 eyes using the IOLMaster. The IOL power was calculated using 3 formulas. IOL power selected based on the Haigis formula calculation using personalized constants which gave the most closely result to plano. Best corrected subjective refraction and ME calculated 1 month after surgery.Results: The Haigis personalized constants for this study were a0 = -0.746, a1 = 0.184, and a2 = 0.208. The ME of SRK/T and Haigis formulas (with and without personalized constant) were -0.09±0.48 D, -0.13±0.36 D, and -0,18±0.37 D. ME percentage of SRK/T and Haigis formulas (with and without personalized constant) maximally reached at ±1.25 D, ±1.00 D, and ±1.25 D. Conclusion: The Haigis formula with personalized constants was more accurate than the Haigis formula without personalized constants in predicting the refractive result of cataract surgery. The accuracy of SRK/T formula is equal to the Haigis formula (with and without personalized constants). Keywords: Haigis formula, SRK/T, personalized constants